Solidification and grain refinement in Ti(48–50)Al2Mn2Nb1B alloys. (October 2018) - Liu, Bo; Li, Jing; Hu, Dawei
Abstract: Two TiAl-based alloys, Ti48Al2Mn2Nb1B and Ti50Al2Mn2Nb1B, were prepared via conventional ingot melting and unidirectional solidification (Bridgman process) to investigate their solidification behaviour and the effect of boron addition on grain refinement. Both of them are found to be α solidifying alloys. Their microstructures are refined, featuring fine and randomly oriented lamellar colonies about 150 μm in size, in conventional ingots but the unidirectionally solidified alloys still have columnar microstructures. The entirely different grain refinement behaviour in ingots and Bridgman samples gave rise to the notion that the enhanced α nucleation from the liquid is the key to grain refinement in the two α solidifying alloys although the specific mechanisms are yet to identify. Highlights: Ti48Al2Mn2Nb1B and Ti50Al2Mn2Nb1B solidify through the α phase. Grain refinement is related to solidification manner in the two alloys. Grain refinement is achieved through enhanced α nucleation from the melt.